Kelainan Hemostasis pada pasien Covid-19 - Hartono Kahar; Nabil Salim (PROCEEDING UMSURABAYA, 2020)
AbstractCoagulopathy in SARS-CoV-2 (Covid-19) patients is an emerge situation to treat because itincreases morbidity and mortality. Increased levels of tPA indicate spontaneous fibrinolysis aswell as a significant increase in Fibrin / Fibrinogen degradation product (FDP) and D-dimerin Covid-19 patients. The invasion of the Covid-19 virus into the endothelial blood vesselscauses endothelial cell dysfunction, a decrease in the fibrinolytic function of the cells, whichpredisposes to thrombus formation. In severe cases, IL-6 which is also released due toendothelial damage predisposes to Sepsis-Induced Coagulopathy (SIC) and DisseminatedIntravascular Coagulation (DIC).Keywords: SARS-CoV-2 (Covid-19), Coagulopathy, SIC, DIC.